2010
DOI: 10.1136/bmj.b5349
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure and circulatory disease risk: Hiroshima and Nagasaki atomic bomb survivor data, 1950-2003

Abstract: Objective To investigate the degree to which ionising radiation confers risk of mortality from heart disease and stroke. Design Prospective cohort study with more than 50 years of follow-up. Setting Atomic bomb survivors in Hiroshima and Nagasaki, Japan. Participants 86 611 Life Span Study cohort members with individually estimated radiation doses from 0 to >3 Gy (86% received <0.2 Gy). Main outcome measures Mortality from stroke or heart disease as the underlying cause of death and doseresponse relations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
380
5
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 432 publications
(441 citation statements)
references
References 54 publications
(77 reference statements)
34
380
5
6
Order By: Relevance
“…Many studies lack this information on lifestyle factors. Of the studies considered in Table 7 only those of the Japanese atomic-bomb survivors [7,48], Mayak workers [49,50], and Canadian fluoroscopy patients [15] had such information. Some lifestyle factors were included in the Nordic breast cancer case-control study [4], and specific medical factors (surgery, thoracoplasty, pneumolobectomy), alcohol consumption, and cigarette smoking were included in the cohort considered here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies lack this information on lifestyle factors. Of the studies considered in Table 7 only those of the Japanese atomic-bomb survivors [7,48], Mayak workers [49,50], and Canadian fluoroscopy patients [15] had such information. Some lifestyle factors were included in the Nordic breast cancer case-control study [4], and specific medical factors (surgery, thoracoplasty, pneumolobectomy), alcohol consumption, and cigarette smoking were included in the cohort considered here.…”
Section: Discussionmentioning
confidence: 99%
“…However, the importance of these findings is unclear, and they may best be interpreted as the effects of chance. In all other radiation-exposed groups with such information there is no evidence that lifestyle factors interacted with radiation risk [4,7,[48][49][50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Nevertheless, in most women, the heart still receives doses of 1 to 5 Gy. [5][6][7][8][9][10][11] Several studies have suggested that exposures at this level can cause is che mic heart disease, [12][13][14] but the magnitude of the risk after any given dose to the heart is uncertain, as are the time to the development of any radiation-related disease and the influence of other cardiac risk factors. We therefore conducted a study relating the risk of is chemic heart disease after radiotherapy to each woman's radiation dose to the heart and to any cardiac risk factors she had at the time of radiotherapy.…”
mentioning
confidence: 99%
“…High total doses to the coronary arteries may cause myocardial infarctions 5-20 years after irradiation. There is no evidence that low doses to large volumes of the myocardium may cause myocardial infarction (Abomb survivor studies) [9].…”
mentioning
confidence: 99%